Enhancing Selectivity and Inhibitory Effects of Chemotherapy Drugs Against Myelogenous Leukemia Cells with Lippia alba Essential Oil Enriched in Citral - Quintero Garcia, Wendy Lorena (2024)
Acute myelogenous leukemia (AML) is one of the most lethal cancers, lacking a definitive curative therapy due to essential constraints related to the toxicity and efficacy of conventional treatments. This study explores the co-adjuvant potential of Lippia alba essential oils (EO) for enhancing the effectiveness and selectivity of two chemotherapy agents (cytarabine and clofarabine) against AML cells. EO derived from L. alba citral chemotype were produced using optimized and standardized environmental and extraction protocols. Rational fractionation techniques were employed to yield bioactive terpene-enriched fractions, guided by relative chemical composition and cytotoxic analysis. Pharmacological interactions were established between these fractions and cytarabine and clofarabine. The study comprehensively evaluated the cytotoxic, genotoxic, oxidative stress, and cell death phenotypes induced by therapies across AML (DA-3ER/GM/EVI1+) cells. The fraction rich in citral (F2) exhibited synergistic pharmacological interactions with the studied chemotherapies, intensifying their selective cytotoxic, genotoxic, and pro-oxidant effects. This shift favored transitioning from necrosis to a programmed cell death phenotype (apoptotic). The F2-clofarabine combination demonstrated remarkable synergistic anti-leukemic performance while preserving cell integrity in healthy cells. The observed selective antiproliferative effects may be attributed to the potential dual prooxidant/antioxidant behavior of citral in L. alba EO.